Broadband 6-μm OPA driven by Yb:CaF2 DPSSL system - Andriukaitis, G. (2013)
6-μJ, 6-μm pulses compressible to 1.5 optical cycles are generated in multistage OPA driven by 500-Hz Yb:CaF2-DPSSL. The system is favorable for verification of the predictions on λ-scaling of photoelectron wavepacket dynamics and atmospheric spectroscopy.